2007
DOI: 10.1080/09583150600937352
|View full text |Cite
|
Sign up to set email alerts
|

Odor specificity testing in the assessment of efficacy and non-target risk forTrichogramma ostriniae(Hymenoptera: Trichogrammatidae)

Abstract: Trichogramma ostriniae Pang and Chen (Hymenoptera: Trichogrammatidae) is an indigenous egg parasitoid of Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) in China. We evaluated T. ostriniae 's responses in olfactometer and wind tunnel assays to various host and plant odors that are likely to impact the efficacy and non-target risk of utilizing T. ostriniae as an augmentative biocontrol agent against Ostrinia nubilalis Hü bner in the USA. In a Yolfactometer, female T. ostriniae exhibited innate positive resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Thus certain parasitoids make use of host pheromones to distinguish between host and non-host. Yong et al (2007) conducted wind tunnel assays to observe the response of an egg parasitoid Trichogramma ostriniae toward the synthetic sex pheromone cues of European corn borer Ostrinia nubilalis Hübner and compared results to that of fall armyworm, Spodoptera frugiperda J. E. Smith before its augmentative release for the control of European corn borer in the USA. The wasp responded to the pheromone of O. nubilalis (reported host since then), a congener to its natural host Asian corn borer, O. furnacalis Guenée found in China, but no such response was observed in case of more distantly related non-target species, that is, fall armyworm.…”
Section: Differentiation Between Host and Non-hostmentioning
confidence: 99%
“…Thus certain parasitoids make use of host pheromones to distinguish between host and non-host. Yong et al (2007) conducted wind tunnel assays to observe the response of an egg parasitoid Trichogramma ostriniae toward the synthetic sex pheromone cues of European corn borer Ostrinia nubilalis Hübner and compared results to that of fall armyworm, Spodoptera frugiperda J. E. Smith before its augmentative release for the control of European corn borer in the USA. The wasp responded to the pheromone of O. nubilalis (reported host since then), a congener to its natural host Asian corn borer, O. furnacalis Guenée found in China, but no such response was observed in case of more distantly related non-target species, that is, fall armyworm.…”
Section: Differentiation Between Host and Non-hostmentioning
confidence: 99%
“…Similarly, Chabi-Olaye et al (2001b) showed that T. isis was more attracted by S. calamistis eggs, when they were offered on maize and sorghum leaf sheaths than on millet leaf sheath, or egg batches without leaf sheaths. In some cases, airborne chemicals or kairmones present on the egg surface have been shown to stimulate an intensive search behavior in egg parasitoids (De Lury et al 1999;Bai et al 2004;Yong et al 2007). Studies by Colazza et al (1997) and Colazza and Rosi (2001) showed that both volatile (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Females of T. brassicae were also found to be responsive to palmitic acid and ethyl palmitate, indicating that different compounds on the host egg may be used for host location (Renou et al 1992). Females of T. ostriniae were shown to respond to accessory glands from mated females besides the extracts and egg masses of the host Ostrinia furnacalis (Guenée) (Bai et al 2004;Yong et al 2007).…”
Section: Volatile Kairomones From Host Eggsmentioning
confidence: 98%
“…Among the Trichogrammatidae, T. brassicae (Renou et al 1989, 1992, Frenoy et al 1992 and T. ostriniae Pang and Chen (Bai et al 2004, Yong et al 2007 were the most investigated. Females of T. brassicae responded in a linear olfactometer to Ostrinia nubilalis Hübner eggs, and to chemical extracts from eggs of O. nubilalis and M. brassicae.…”
Section: Volatile Kairomones From Host Eggsmentioning
confidence: 99%